Potential of Yields and Starch Production from Several Local Cassava Genotypes - Hartati - Hartati; N Sri Hartati (Bioscience, 2019)
The need for cassava starch is increasing along with its aplication in industries. Our study aim to determine the yield and production of starch from several local cassava genotypes. Forty-one cassava genotypes from LIPI collection were used to produce starch. Cassava tubers were harvested from five trees of each genotype. The number and the weight of tuber from each genotypes were then calculated. Around 2500 grams of tuber from each genotypes were grated and extracted to produce the starch. The results showed that cassava with the highest yield was Kristal Merah (15,460 Kg), and followed by PNG1 (15,1Kg), Menti (9,970Kg) and Roti (9,380Kg). The genotype with the highest tuber weight is PNG1, and then followed by Roti , Menti  and Kristal Merah. Eleven genotypes of cassava produced starch with levels above 25%. Based on our results, the genotypes that potentially used as raw material for the starch industry were Kristal Merah, PNG, Menti and Roti.Keywords: cassava, genotypes,  starch, tuber’s weight, yield